Performance of stock portfolio based on contrarian strategy in indonesia stock exchange - Pratama, I Gede Wira; Rahyuda, Henny (International research journal of management, IT and social sciences, 2019)
This study aims to determine the differences in the performance of high abnormal stock portfolio during the test period compared with the performance of the stock portfolio in the formation period, the difference in the performance of the low abnormal return of the test period compared to the portfolio performance of the stock formation period, as well as the difference in the performance of the high abnormal return stock portfolio (winner) compared with a low abnormal return (loser) test period. The sample consists of shares included in the Kompas 100 index which are listed on the Indonesia Stock Exchange. The sampling method used in this study is a tiered sampling method that is analyzed by means of the two different test. The results showed that within a period of 12 months, there was a positive difference of 10.59% in the loser stock portfolio against the winner stock portfolio in the next period. Stocks that initially had low abnormal returns (losers) experienced a greater return reversal than the winner stock portfolio return in the next period, indicating a market anomaly associated with the overreaction hypothesis.